Immediate Postpartum Insertion of Copper Intrauterine Device in a Brazilian University Hospital: Expulsion and Continuation Rates - Nahas, Georgia [UNESP]; Magalhães, Claudia [UNESP]; Bueloni-Dias, Flavia [UNESP]; Nahas, Eliana [UNESP]; Borges, Vera [UNESP] (Federação das Associações de Ginecologia e Obstetrícia, 2023)
Objective To evaluate the expulsion and continuation rates of the copper intrauterine device (IUD) inserted in the immediate postpartum period in a Brazilian public university hospital. Materials and Methods In the present cohort study, we included women who received immediate postpartum IUD at vaginal delivery or cesarean s March 2018 to December 2019. Clinical data and the findings of transvaginal ultrasound (US) scans performed 6-weeks postpartum were collected. The expulsion and continuation rates were assessed 6-months postpartum using data from the electronic medical records or by telephone contact. The primary outcome was the proportion of IUDs expelled at 6 months. For the statistical analysis, we used the Student t -test, the Poisson distribution, and the Chi-squared test. Results There were 3,728 births in the period, and 352 IUD insertions were performed, totaling a rate of 9.4%. At 6 weeks postpartum, the IUD was properly positioned in 65.1% of the cases, in 10.8% there was partial expulsion, and in 8.5% it had been completely expelled. At 6 months postpartum, information was obtained from 234 women, 74.4% of whom used IUD, with an overall expulsion rate of 25.6%. The expulsion rate was higher after vaginal delivery when compared with cesarean section (68.4% versus 31.6% respectively; p = 0.031). There were no differences in terms of age, parity, gestational age, final body mass index, and newborn weight. Conclusion Despite the low insertion rate of copper IUDs in the postpartum period and a higher expulsion rate, the rate of long-term continuation of intrauterine contraception was high, indicating that it is a useful intervention to prevent unwanted pregnancies and to reduce short-interval birth.
Insercao de dispositivo intrauterino de cobre no pos-parto imediato em hospital universitario brasileiro: Taxas de expulsao e continuacao
Keywords: continuation rate; cooper intrauterine device; expulsion rate; immediate postpartum insertion; postpartum contraception